Defects and oxygen vacancies tailored structural, optical and electronic structure properties of Co-doped ZnO nanoparticle samples probed using soft X-ray absorption spectroscopy. (September 2020) - Sahu, Jyoti; Soni, Swati; Kumar, Sudhish; Dalela, B.; Alvi, P.A.; Sharma, S.S.; Phase, D.M.; Gupta, M.; Kumar, Shalendra; Dalela, S.
Abstract: The structural, optical and electronic structure properties of all the Zn1-x Cox O nanoparticles [x = 0.01, 0.03, and 0.05], synthesized using co-precipitation method have been studied using X-ray diffraction (XRD), Surface Enhanced Raman Spectroscopy (SERS), UV–Vis–NIR spectroscopy and X-ray Absorption Spectroscopy measurements. The XRD and SERS analysis have confirmed the formation of hexagonal wurtzite structure (space group C 4 6v ). UV–Vis–NIR spectra indicate the blue shifting of the absorbance edge and the band gap is found to decrease with doping. The electronic structure of undoped and Co-doped ZnO nanoparticles have been investigated using site selective and element sensitive X-ray absorption spectroscopy. From the XAS spectra at Zn L3, 2, Co L3, 2 and O K-edges we have found that Zn ions are in +2 valence state in undoped and Co-doped ZnO nanoparticles. From the XAS analysis it can be seen that proper incorporation of Co-ion in the host lattice take place in t2g eg state Co +2 (d 7 ) under tetrahedral symmetry and maintain the crystal symmetry with lattice distortion. The Co-ion doping in the ZnO nano-matrix leads to creation of various defects & oxygen vacancies, which results in the blue shift in band-gap energy makes them useful for various applications e.g. photocatalytic water splitting, hydrogen generation, spintronics and optoelectronics. Highlights: Co-doped ZnO nanomaterials, synthesized using co-precipitation method. Material Characterization using X-ray diffraction, Transmission electron microscopy, Raman and X-ray Absorption spectroscopy. XRD and Raman analysis confirms formation of hexagonal wurtzite structure (space group C 4 6v ) with Co +2 ions in ZnO lattice. Absorption spectra indicate the blue shifting of the edge with doping. The Zn and Co valence state is +2 confirmed by XAS at Zn L3, 2, Co L3, 2  and O K edges with introduction of oxygen vacancies.